Effect of Serum Phosphate on the Prognosis of Septic Patients: A Retrospective Study Based on MIMIC-IV Database - Li, Zhaoyang; Shen, Tingwen; Han, Yi (Frontiers in Medicine, 2022)
Objective: To assess the effect of serum inorganic phosphate (Pi) on the prognosis of septic patients. Methods: A retrospective analysis of septic patients selected from the Medical Information Mart for Intensive Care (MIMIC)-IV database was performed. Sepsis was diagnosed according to the Third International Consensus Definition for sepsis and septic shock (Sepsis-3). The time weighted values of serum Pi measurements within the first 24 hours of sepsis were analyzed. The association between serum Pi and in-hospital mortality was evaluated with generalized linear model (log-binomial model). Results: Analysis of 11658 patients from 6 ICUs showed a nearly linear correlation between serum Pi and in-hospital mortality in all septic patients ，especially in septic patients with AKI. The increase of serum Pi was related to higher risk of AKI, higher norepinephrine doses, ICU mortality and in-hospital mortality. The generalized linear model showed that serum Pi was an independent predictor for in-hospital mortality in all septic patients even within normal range. The adjusted risk ratios (RRs) were also significant in subgroup analyses according to kidney function, gender, respiratory infection, vasopressor use, and SOFA score. Conclusion: Higher levels of serum Pi, even within normal range, were significantly associated with higher risk of in-hospital mortality in septic patients regardless of kidney function, gender, respiratory infection, vasopressor use, and SOFA score.